Snapin promotes HIV‐1 transmission from dendritic cells by dampening TLR8 signaling. (16th October 2017) - Khatamzas, Elham; Hipp, Madeleine Maria; Gaughan, Daniel; Pichulik, Tica; Leslie, Alasdair; Fernandes, Ricardo A; Muraro, Daniele; Booth, Sarah; Zausmer, Kieran; Sun, Mei‐Yi; Kessler, Benedikt; Rowland‐Jones, Sarah; et al.
Abstract: HIV‐1 traffics through dendritic cells (DCs) en route to establishing a productive infection in T lymphocytes but fails to induce an innate immune response. Within DC endosomes, HIV‐1 somehow evades detection by the pattern‐recognition receptor (PRR) Toll‐like receptor 8 (TLR8). Using a phosphoproteomic approach, we identified a robust and diverse signaling cascade triggered by HIV‐1 upon entry into human DCs. A secondary siRNA screen of the identified signaling factors revealed several new mediators of HIV‐1 trans ‐infection of CD4 + T cells in DCs, including the dynein motor protein Snapin. Inhibition of Snapin enhanced localization of HIV‐1 with TLR8 + early endosomes, triggered a pro‐inflammatory response, and inhibited trans ‐infection of CD4 + T cells. Snapin inhibited TLR8 signaling in the absence of HIV‐1 and is a general regulator of endosomal maturation. Thus, we identify a new mechanism of innate immune sensing by TLR8 in DCs, which is exploited by HIV‐1 to promote transmission. Synopsis: HIV‐1 evades detection by the innate immune system in dendritic cells (DCs) to facilitate spreading to T lymphocytes. A phosphoproteomic and secondary siRNA screen identifies signaling pathways induced by HIV‐1 in DCs and shows that Snapin is a mediator of HIV‐1 transmission. Phosphoproteomics map an HIV‐1 signalosome induced on viral entry to DCs. Secondary siRNA screen identifies the dynein motor Snapin as a mediator of HIV‐1 transmission to CD4 + T cells. Snapin reduces HIV‐1 localization with TLR8‐expressing early endosomes. Snapin dampens HIV‐1‐mediated pro‐inflammatory responses in DCs. Abstract : A proteomic and siRNA screen identifies signalling components required for HIV‐1 evasion of the host innate immune response in dendritic cells.